The Case Study on Significance of Daylight in Classroom Setting at Sarajevo Campus - Ahmed Obralic; Salam Jeghel (European Scientific Journal, ESJ, 2021)
When designing schools, universities, or any educational centers, daylight in classrooms is usually one of the essential issues that take the architect's attention. Its importance comes from the fact that daylight can impact students' health, mood, and visual performance. Providing an appropriate amount of uniformly distributed light with glare protection is a significant factor in classroom design (Zomorodian Z S, 2016). This study is based on a literature review, studies, and articles researching the effect of daylight in a classroom environment on students' performance. It tends to define the significance of daylight design in the learning environment. This paper also deals with specifying and exploring all the conditions, factors, and elements that contribute to creating this successful daylight design in classrooms. Besides, it investigates the daylight design of the buildings at the campus of Sarajevo that will, later on, contribute to the creation of a design manual of all the considerations that need to be taken for schools and educational centers’ daylight design. The study is conducted at the campus of Sarajevo in the academic year 2019. The literature review, data study, and previous studies define the significance of daylight in the classroom environment and show the correlation between daylight and students' achievement in the classroom environment. It defines the elements and conditions of successful daylight design in classroom settings. The study explored the current state of the daylight design at the campus of Sarajevo detecting its lacks and obstacles regarding adequate illumination. Based on the literature review, an appropriate solution for the investigated classroom environment has been designed.